Analisis Pengembalian Klaim BPJS Rawat Inap Dengan Metode PDCA di RS Jember Klinik - Atma Deharja; Ayu Imelda Rosita; Rossalina Adi Wijayanti; Maya Weka Santi (Politeknik Negeri Jember, 2022)
Health financing is one of the important things in the implementation of the National Health Insurance, which is held in hospitals by the Health Social Security Administering Body through the submission of claims. The file submitted was not fully confirmed, resulting in the return of the claim file. This happened at the Jember Clinic Hospital, inpatient claimed files pending for 3 months an average of 8%. The purpose of this study analyzes the return of inpatient claim files by social security administrator health verifiers with the (Plan, Do, Check, Action) approached at Clinic Hospital Jember. The type of research was qualitative. Data collection through interviews, observations, questionnaires, documentation and brainstorming conducted to four informants. The results of the identification of the factors causing the return of inpatient claim files were caused by several things, one was the patient administrative discrepancy. The planning carried out in this research was making checklist sheet for completeness of claim files, makimg Standard Operating Procedures for completeness of claim files and making a request form for the completeness of the claim files. Based on the results of the planning implementation that had been carried out, the return of the claim file was still quite high because it was not in accordance with the target set by the researcher. Recommendations from this study was to minimize the return of claim files, namely to include training for related officers, making Standard Operating Procedures related to claim process systematically and carried out computer maintenance regularly.